Pengaruh Karakteristik Perusahaan Terhadap Nilai Perusahaan Sub Sektor Transportasi di Bursa Efek Indonesia - Siti Asiyah; Rizky Fadhlina Putri; Sri Fitria Jayusman (Jurnal Multidisiplin Madani, 2022)
The purpose of this study was to determine the effect of leverage, profitability and company growth on firm value. Firm value in this study is proxied by price book value (PBV). The population obtained is 43 companies in the transportation sub-sector on the Indonesia Stock Exchange in 2016-2018. The sample was taken using a purposive sampling technique and a total sample of 12 companies during the transportation sub-sector for three years of observation 2016-2018. The total number of data is 12 x 3: 36 data that matches the criteria. The analysis technique uses classical assumption test and multiple regression analysis. Based on the results of the study, it is known that leverage and profitability have no effect on firm value, while firm growth has an effect on firm value.